Synthesis of 5-ethyl-carbamyl-2,2-dimethyl-1,3 benzodioxoles as an insecticide - ., Sumantri (Indonesian Journal of Pharmacy, 2005)
The imported insecticides which are commonly used such as carbamate, organophosphate and organochlorine insecticides, have a high level of toxicity, and persist in the environment for a long period of time. The research aims to synthesize a possible insecticide that is 5-ethyl-carbamyl-2,2-dimethyl-1,3- benzodioxole, which is expected to perform a low level toxicity since it contains benzodioxole moiety which has natural antioxidant activity and also functions as insecticide synergist.The compound was synthesized by nitration of 2,2-dimethyl-1,3-benzodioxole as the condensation product between catechol and propanon-2, which was followed by reduction with Zn and HCl, and acylation using ethylchloroformate in triethylamine. The product obtained from the synthesis was purified by column chromatography, then elucidation of structure was carried out by spectroscopic method. The products obtained were also analysed by gas chromatographic and GCMS methods.The results indicate that the product 5-ethylcarbamyl-2,-dimethyl-1,3- benzodioxole can be synthesized by condensation reaction of 2,2-dime-thyl-1,3-benzodioxole, then folowed by nitration of 2,2-dimethyl-1,3-benzodioxole, reduction of 5-nitro-2,2-dimethyl-1,3-benzodioxole, and acylationof 5- amino-2,2- dimethyl-1,3-benzodioxole. The yield obtained was 15,02%.Key words: synthesis, 5-ethylcarbamyl-2,2-dimethyl-1,3-benzodioxole, insecticide